Examining the synergies implication of merger and acquisition in banking sector: evidence from emerging economy - Verma, M.; Kalyan, P.; Ekka, P.M. (International Journal of Accounting & Business Finance, 2023)
Mergers and acquisitions (M&A) have lately increased in the Indian banking sector with the desire to improve efficiency. It is important to investigate whether the banks are able to gain expected synergies. This study examines the effects of M&A in the banking sector by analyzing M&A transactions between 2014 and 2022. The current paper is built on secondary financial data, whereas outcomes were assessed on three major parameters, i.e. market performance, financial performance, and overall efficiency improvement. The study used different methodologies such as event study, ratio analysis, tabulation, and Wilcoxon rank text to check over different parameters. The findings reveal a significant improvement in market performance and financial performance. No statistically significant improvements were found in profitability, liquidity, and operational efficiency. We conclude that synergy gain cannot be achieved by M&A only. Overall the study gives insight into the value creation through M&A in emerging economies' banking industry and emphasizes the importance of effective integration strategies. The study has implications for the central bank, banks, and policymakers in emerging economies to decide on M&A activities and the development of a robust banking sector.
Keywords: Economic Value Added; Event Study; Market Performance; Mergers and Acquisitions; Operating Efficiency